Peach Scab - Daniel Mancero-Castillo; Ali Sarkhosh; Mercy Olmstead; Philip Harmon (EDIS)
There are many peach diseases that can affect fruit quality and the marketability of the produce. Blemishes to the skin or within the flesh can be a reason to reject an entire fruit load or significantly reduce the purchasing price.